The question why and how people differ in personality cannot be answered satisfactorily while neglecting biological approaches. (February 2022) - Reuter, Martin; Plieger, Thomas; Netter, Petra
Abstract : The present opinion paper makes a strong case for a biologically oriented personality theory. A short review on seminal studies applying methods from the neurosciences to unravel the biological underpinnings of personality is given, and findings are critically discussed. It becomes apparent that new methodological advances in the neurosciences provide inspiration for modern personality research but that there is still so much unexplained variance left. Only interdisciplinary research can be a promising research avenue for the future.